The Unheard Story of a Last-Mile Teacher: Translanguaging in English Language Teaching - Villamor, Sonny (Adabuna : Jurnal Pemikiran dan Pendidikan, 2025)
Translanguaging has emerged as a significant pedagogical approach in multilingual classrooms, allowing learners to fluidly navigate between languages to enhance comprehension and engagement. In linguistically diverse settings, particularly those involving indigenous learners, translanguaging serves as a bridge between students’ home languages and the target language, fostering more inclusive and effective learning experiences. This study explores an English teacher’s perceptions, applications, and challenges in implementing translanguaging in a multilingual classroom. Using a narrative qualitative approach and purposive sampling, the study focused on an English teacher at Hinandayan National High School, Agusan del Norte, who has experience teaching Higaonon learners. Thematic analysis was employed to examine the data. Findings indicate that while the teacher perceives translanguaging as beneficial for enhancing learners' comprehension, some students still struggle to improve their English academic performance. The teacher frequently relied on translation to facilitate understanding, yet specific translanguaging strategies were not explicitly employed due to a lack of formal training. A major challenge arose in writing activities, as learners preferred to use their mother tongue, requiring the teacher to reinforce the importance of English usage. The study recommends selectively integrating translanguaging for learners struggling with English comprehension and providing teachers with specialized training to maximize its effectiveness.